Measured-based shaker model to virtually simulate vibration sine test. (December 2016) - Hoffait, Sébastien; Marin, Frédéric; Simon, Daniel; Peeters, Bart; Golinval, Jean-Claude
Abstract: During high level vibration test on a high mass specimen, the test engineer is often facing difficulty to pass properly the specified vibration level due to coupling between the specimen and the shaker. The present paper present a methodology to define a virtual shaker testing simulator. The first step involves the dynamic identification of a 80 kN shaker performed thanks to measurements (modal analysis and sine sweep). The second step is the definition of the physic represented in the simulator and the translation of the electromechanical equations in a home-made simulator. Controller developed by SIEMENS LMS and supplied to V2i for a use in the framework of the AOC project is introduced to close the loop. Two test cases are described to demonstrate the possibilities offered by the simulator.